STUDENTS’ METACOGNITIVE AWARENESS ON LISTENING : SURVEY ON ENGLISH DEPARTMENT STUDENTS - Hesti Intan Rohmatika; Siti Asiyah; Diyah Atiek Mustikawati; Ana Maghfiroh (IKIP Siliwangi, 2021)
Metacognitive awareness is a cognitive evaluation of students' impressions of themselves during listening activities in the form of their comprehension, goals, and strategies to enhance listening abilities. The purpose of this study was to discover what metacognitive awareness strategies students frequently use in their listening performances. The subject in this study was the students of the 4th semester of English Department, Muhammadiyah University of Ponorogo, who took the Listening for authentic materials course. The study used quantitative correlational research design with the data collected from questionnaire which adopted and elaborated from Vandergrift et al. The respondent who filled out the questionnaire was 10 of the 15 existing students. The results showed that students’ metacognitive awareness in listening strategies were classified into: problem solving (4.67), directed attention (4.13), planning / evaluation (4.10), mental translation (4.03), and person knowledge (3.60). It indicated that most English Department students used problem solving as their listening strategy. It also showed that students frequently use their understanding about the context rather than translating word for word in their heads; comparing the impact of their listening efforts; sustaining concentration and remaining focused on listening. Keywords: Metacognitive Awareness, Listening Strategy, Metacognition, EFL